Gene structure, recombinant expression and function characterization of Siniperca chuatsi Fsrp‐3. Issue 5 (1st March 2019) - Wang, Jianhua; Cheng, Jia; Li, Yulong; Yan, Huiling; Wu, Ping; Zhu, Xin; Liu, Li; Chen, Lin; Chu, Wuying; Zhang, Jianshe
Abstract : A full‐length complementary (c)DNA sequence encoding follistatin‐related protein 3 ( fsrp‐3 ) was determined from skeletal muscle in Chinese mandarin fish Siniperca chuatsi, its molecular structure was characterised and its function suggested. The putative structure of S. chuatsi Fsrp‐3 contains an N‐terminal domain and two follistatin domains. Quantitative reverse‐transcription (qRT)‐PCR assays revealed that fsrp‐3 messenger (m)RNA was differentially expressed among assayed tissues and was highly expressed in heart and intestine. fsrp‐3 mRNA exhibited increasing expression from the larval to the juvenile stage (500 g). To investigate the potential function of S. chuatsi fsrp‐3 in muscle growth, we constructed a Fsrp‐3 prokaryotic expression system and injected the purified Fsrp‐3 fusion protein into the dorsal muscle. Fsrp‐3 administration significantly influenced cross‐section area, satellite cell activation frequency and nuclear density of S. chuatsi muscle fibres. Following Fsrp‐3 treatment, the expression of myogenic regulatory factors was up‐regulated and decline in the expression of myostatin was observed. The study revealed that Fsrp‐3 may affect muscle growth by regulating myogenic regulatory factor expression and antagonizing myostatin function to initiate satellite cell activation and differentiation in S. chuatsi .